Penetapan Upah Minimum oleh Pengusaha Bisnis Kuliner yang Memiliki Surat Izin Usaha di Kabupaten Jember - Permata, Anggia; Wahjuni, Edi; Fahamsyah, Ermanto (Lentera Hukum, 2017)
Entrepreneurs of culinary business must have employees so their business can run smoothly. Additionally, they must also have a business license, as part of their legal obedience. Some of their legal responsibilities include the payment of minimum salary for employees, stated in regulations. In a practical matter, the payment of minimum wages faces problems, especially for small and medium business enterprises. This minimum wages' research is undertaken based on laws which set about employment, determination of minimum wages by culinary businesses, and legal solutions that employees can do if they did not get minimum wages salary. This research also uses the interview to collect data. Some of the respondents being interviewed are someone who has better knowledge about these problems. The conclusions from this research that salary payment is a never-ending problems, the things that entrepreneur’s thought fair for them but it’s unfair or employees, like minimum wages payments. Employees who did not get minimum wages salary choose to not reporting that, and quit their jobs. Keywords: Culinary businesses, Salary, Minimum Wages, and Employees